Genetic variability of Amorphophallus muelleri Blume in Java based on Random Amplified Polymorphic DNA - YUYU SURYASARI POERBA; DIYAH MARTANTI (Biodiversitas Journal of Biological Diversity, 2008)
Amorphophallus muelleri Blume (Araceae) is valued for its glucomanan content for use in food industry (healthy diet food), paper industry, pharmacy and cosmetics. The species is triploid (2n=3x=39) and the seed is developed apomictically. The present research is aimed to identify genetic variability of six population of A. muelleri from Java (consisted of 50 accessions) using random amplified polymorphic DNA (RAPD). The six populations of the species are: East Java: (1) Silo-Jember, (2) Saradan-Madiun, (3) IPB (cultivated, from Saradan- Madiun), (4) Panti-Jember, (5) Probolinggo; and Central Java: (6) Cilacap. The results showed that five RAPD primers generated 42 scorable bands of which 29 (69.05%) were polymorphic. Size of the bands varied from 300bp to 1.5kbp. The 50 accessions of A. muelleri were divided into two main clusters, some of them were grouped based on their populations, and some others were not. The range of individual genetic dissimilarity was from 0.02 to 0.36. The results showed that among six populations investigated, Saradan population showed the highest levels of genetic variation with mean values of na = 1.500+0.5061, ne = 1.3174+0.3841, PLP = 50% and He = 0, 0.1832+0.2054, whereas Silo-Jember population showed the lowest levels of genetic variation with mean values na = 1.2619+0.4450, ne =1.1890+0.3507, PLP = 26.19% and He = 0.1048+0.1887. Efforts to conserve, domesticate, cultivate and improve genetically should be based on the genetic properties of each population and individual within population, especially Saradan population which has the highest levels of genetic variation, need more attention for its conservation.Key words: Amorphophallus muelleri, RAPD, genetic variability.